Ergonomic Evaluation of Manual Coconut Dehuskers - ANSILA K.A ATHIRA KONDARAN KADAVATH SETHULAKSHMI K.M; Er. Suma Nair (Guide) (Tavanur 2017 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Ergonomic Evaluation of Manual Coconut Dehuskers
Ergonomic Evaluation of Manual Coconut Dehuskers